The Relationship Between Organizational Involvement And Adaptability In Educational Hospitals Of Kerman In 2012 - Mahmoud Nekoei-Moghadam; Sajad Delavari; Mohammad Hossein Ghorbani; Somaye Delavari; Mozhgan Fardid (Tehran University of Medical Sciences, 2015)
Background and Aim: Employee involvement and organizational adaptability are two key factors towards success in almost all organizations. Hospital managers must pay special attention to these two variables and always try to improve them. The present research, therefore, studies the relationship between employee involvement (empowerment, team orientation, and capability development) and organizational adaptability (creating change, customer focus, and organizational learning) in the educational hospitals of Kerman. Materials and Methods: The population of this quantitative study includes all staff members of Kerman's educational hospitals, estimated about 1370 individuals. A sample of 302 subjects was systematically selected based on Krejcie and Morgan's table of sample size. The data collection tool was a questionnaire and the data were analyzed by Pearson correlation coefficient, ANOVA, and Schefe post hoc test. Results: According to the findings, employee involvement and organizational adaptability -- and their related indices -- were at an acceptable level and were almost equal to those of international organizations. Moreover, there was a positive and significant relationship between these two main variables and their related indices. Conclusion: The results of this study can help hospital managers to verify the present situation of organizational adaptability and organizational involvement and their relationship. These findings could help hospitals to predict change priorities and select better strategies.